2017
DOI: 10.1111/ejn.13614
|View full text |Cite
|
Sign up to set email alerts
|

Cx36, Cx43 and Cx45 in mouse and rat cerebellar cortex: species‐specific expression, compensation in Cx36 null mice and co‐localization in neurons vs. glia

Abstract: Electrical synapses formed by connexin36 (Cx36)-containing gap junctions between interneurons in the cerebellar cortex have been well characterized, including those formed between basket cells and between Golgi cells, and there is gene reporter-based evidence for the expression of connexin45 (Cx45) in the cerebellar molecular layer. Here, we used immunofluorescence approaches to further investigate expression patterns of Cx36 and Cx45 in this layer and to examine localization relationships of these connexins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 75 publications
(145 reference statements)
2
7
0
Order By: Relevance
“…Gap junction proteins are widely expressed in the cerebellum of developing and adult vertebrates. Cx36, the mammalian homolog of Gjd2b has been shown to be expressed in the rodent cerebellar cortex in the molecular layer and granule cell layer (Belluardo et al, 2000;Degen et al, 2004;Nagy and Rash, 2017), and Cx36 puncta were observed localized to Purkinje neurons (Alcami and Marty, 2013), although the mRNA was not found in Purkinje neurons (Belluardo et al, 2000). In larval zebrafish, cell type specific transcriptome analysis in larval zebrafish revealed gjd2b expression in PNs, granule cells, eurydendroid cells and Bergmann glial cells (Takeuchi et al, 2016).…”
Section: Gap Junctions In Pnsmentioning
confidence: 99%
“…Gap junction proteins are widely expressed in the cerebellum of developing and adult vertebrates. Cx36, the mammalian homolog of Gjd2b has been shown to be expressed in the rodent cerebellar cortex in the molecular layer and granule cell layer (Belluardo et al, 2000;Degen et al, 2004;Nagy and Rash, 2017), and Cx36 puncta were observed localized to Purkinje neurons (Alcami and Marty, 2013), although the mRNA was not found in Purkinje neurons (Belluardo et al, 2000). In larval zebrafish, cell type specific transcriptome analysis in larval zebrafish revealed gjd2b expression in PNs, granule cells, eurydendroid cells and Bergmann glial cells (Takeuchi et al, 2016).…”
Section: Gap Junctions In Pnsmentioning
confidence: 99%
“…It remains possible that gap junction coupling between PC axons is present (Middleton et al, 2008;Traub et al, 2008). However, electrical coupling between pairs of PCs has never been observed, and PCs do not express Connexin 36 (Belluardo et De Zeeuw et al, 2008;Nagy and Rash, 2017), which mediates most electrical coupling between neurons. Gap junction coupling between PCs would therefore have to be mediated by an unidentified mechanism that couples their axons in a manner that cannot be detected with somatic recordings and does not lead to dye coupling between cells (De Zeeuw et al, 2008).…”
Section: Evidence Supporting Ephaptic Couplingmentioning
confidence: 99%
“…In rodents, few studies have reported dye-coupling of PNs to other PNs or to other cell types in the cerebellar cortex [4245]. Cx36, the mammalian homolog of Gjd2b has been shown to be expressed in the cerebellar cortex in the molecular layer and granule cell layer [4648], although the mRNA was not found in Purkinje neurons [46]. From these studies, it appears that PNs in fish and mammals are electrically coupled to other neurons, while there may be species-specific differences in the molecular components of these electrical synapses.…”
Section: Discussionmentioning
confidence: 99%